COVID-19: An Ophthalmologist’s Perspective: COVID-19: A Perspetiva do Oftalmologista - Cunha, João Paulo; Coelho, Nuno Moura; Proença, Rita Pinto; Santos, Arnaldo Dias; Ferreira, Joana Tavares (Gazeta Médica, 2020)
In just one hundred years, the world has been through five pandemics. Lessons of the past have not prevented a new virus from being responsible for a fifth wave of deaths worldwide, even with scientific advances and the rapid response of societies that, for the most part, anticipated the political and economic response. A century after the end of the Spanish Flu (1918/19), in December 2019, the world has watched the beginning of the second pandemic of the 21st century, coronavirus disease 2019 (COVID-19) caused by a new severe acute respiratory coronavirus syndrome-2 (SARS-CoV-2). The eye can not only be the entry point for coronaviruses, but also a target organ. Conjunctivitis, uveitis, vasculitis, retinitis and optic neuritis have all been documented in animal models studies. In this article, we review the possible roles of the visual system/ocular tissues as an entryway, and the potential ophthalmic manifestations of human SARS-CoV-2 infections. This review article will also highlight the most effective ways for protecting and preventing the spread of the virus.